Sociological Strategy of Da'wah in Marginalized Communities - Muhammad Yusuf; Mahmuddin (Universitas Muhammadiyah Palu, 2025)
The success of developing a da'wah strategy is supported by various factors, one of which is a da'wah strategy that hits the target. The most effective da'wah strategy used in marginalized communities is through coaching in the form of direction, mentoring and mentoring in understanding Islamic teachings, providing an understanding of the Islamic religion and its straightforward explanations based on the Qur'an and al-Hadith, establishing cooperation with religious organizations (Islam) and ulama/kyai in the context of developing da'wah through da'wah strategies, namely the al-hikmah method, the bi al-lisan method, the al-mujjadi billati hiya ahsan method and the bill-things. Marginal communities or the fringes are a group of people who are marginalized, especially from an economic aspect. This occurs as a result of the impact of development policies that are too top down (coming from government authorities) without properly considering what the lowerclass people really want and need. Not to mention the problems that exist within the lower classes of society who are unable to adapt and involve themselves in the development process. This inability is caused by education and skills factors that are far from adequate.